Prevalence and determinants of diabetes mellitus in high altitude: A cross sectional study in mountainous region of Nepal - Acharya, Kiran Prasad; Prajapati, Dipankar; Sherpa, Kunjang; Khanal, Aarjan; Poudel, Pratima; Hirachan, Anish; Bogati, Amrit; Adhikari, Chandra Mani (Asian Journal of Medical Sciences, 2020)
Background: There had been many studies depicting variations in the prevalence of diabetes mellitus in Nepal ranging from 1.4% to 19%. However, the pooled prevalence was found to be 8.4%. There are only few studies done till date in our part of the world to study the actual prevalence and determinants of Type 2 Diabetes Mellitus ( DM-2) in people residing in mountains. Aims and Objectives: This study was conducted with to estimate the prevalence and determinants of diabetes mellitus among the high-altitude populationin Jomsom district of Nepal. Materials and Methods: A cross sectional study was carried out in Jomsom district of Nepal, at an altitude of 2743 meters on 4th and 5thof June, 2017 . A detailed history from the participants of their past medical illness including diabetes mellitus and hypertension was taken. In addition, blood sugar level, blood pressure, anthropometric variables like weight, height, BMI, Waist, Hip, Waist/hip ratio were documented after the verbal consent of the participants. Results: A total of 617 local residents of Jomsom were enrolled in the study. The mean age of study population was 44.4±17. 6 years with female to male ratio being 1.15:1 (53.5% vs 46.5% male). The prevalence of diabetes mellitus was found to be 5.2%, which was significantly lower than the overall prevalence of diabetes in the Nepalese population which is 8.4%. Male population was found to have higher prevalence of diabetes in our study. Higher BMI and waist/hip ratio were also associated with increased incidence of diabetes mellitus. This study revealed that compared with individuals with a normal BMI, individuals who were overweight or obese were more likely to be diagnosed with DM-2 (OR [95%CI]: ranging from 4.33 [0.96–19.46] for overweight adults to 7.76 [1.76–34.13] for adults in Obesity. Conclusion: The overall prevalence of diabetes mellitus is lower among the individuals residing in higher altitude compared to the general population although the other determinants are comparable.